ESTUDIO JURIDICO, DOCTRINARIO Y DE DERECHO COMPARADO CON LOS PAÍSES DE EL SALVADOR Y COLOMBIA; EN EL CONTEXTO DEL TRATAMIENTO PENAL DE LA EXTORSIÓN EN EL ECUADOR. - Peñafiel Jiménez, Génesis Janinna (2024)
The following work is titled "Legal, doctrinal, and comparative law study with El Salvador and Colombia; in the context of criminal treatment of extortion in Ecuador." Its interest in researching and conducting a legal study arises from the evidence of the violation of certain legal interests such as the right to life, physical integrity, and the property of Ecuadorian citizens. Currently, our country is heavily affected by organized crime, which is causing terror to all citizens with new forms of extortion. This situation stems from the increase in the crime rate in the country; the rising number of extortion- related crimes has reached alarming levels that require stricter penal treatment. Therefore, this research aims to compare different approaches adopted by countries like El Salvador and Colombia, as they have implemented different measures and actions in their legislation regarding the criminal offense of extortion, compared to our country. In the current course of this work, materials and methods are applied to conduct research, including interviews and surveys with legal professionals.